Anglican Evangelicals and Revival, 1945–59 - Chapman, Alister (Studies in church history, 2008)
This essay is a study of the religious revival that didn’t quite happen in Britain after the Second World War. It focuses on conservative evangelical Anglicans, whose own renaissance during these years puts them at the centre of discussions about the post-war increase in churchgoing. Its central contention is that human agency and cultural peculiarities are just as important for understanding this chapter of English religious history as any seemingly inexorable, broad-based social changes inimical to religious practice. More particularly, the chapter focuses on Anglican evangelical clergy and their attitudes to religious revival. In so doing, it highlights the fact that the practices and prejudices of church people are an essential part of the story of post-war English religious life. Scholars looking to explain religious malaise in post-war Britain have frequently looked everywhere except the decisions made by the churches and their leaders, the assumption seeming to be that because decline was unavoidable there was nothing pastors, priests or their congregations could do to stem the tide. This chapter seeks to redress the balance by examining the ways in which evangelical Anglican clergy pursued revival in England, some of the obstacles they faced in this pursuit, and how they responded when they felt they had failed. Among the things they discovered was that ‘revival’ was a word to be handled with care.